Natural Law and Protestant Reform: Lessons from the Forgotten Reformer1. Issue 3 (August 2019) - Charles, J. Daryl
Despite Protestants' suspicion of natural law ethics in their recent history, there are signs that in some Protestant circles a re-awakening to the importance of natural law is occurring. This is as it should be, given the fact that the magisterial reformers of the 16th century all affirmed without equivocation the natural law. Foremost among these champions was the forgotten reformer, Phillip Melanchthon, whose remarkable output and influence during the 16th century were unparalleled and whose emphasis on natural law reasoning was notable.